Out-of-the-Box Medical Device Safety. Issue 1 (June 2016) - Clark, Shannon; Natesan, Divya; Walker, Morgan; Forkey, Denise
Out-of-the-box experience is an important consideration in medical device design that not only impacts the user's impression of the product, but can also have critical safety implications. This article discusses the basic safety questions to contemplate in a use-related risk analysis pertaining to the out-of-the-box experience, and focuses on how the most critical safety risks can be reduced or eliminated by conducting a usability study related to the out-of-the-box experience.